Reply to: Comment on Predicting In‐Hospital Mortality in COVID‐19 Older Patients with Specifically Developed Scores. Issue 4 (22nd January 2021) - Covino, Marcello; De Matteis, Giuseppe; Burzo, Maria Livia; Franceschi, Francesco; Sandroni, Claudio
Abstract : This letter comments on the letter by Alain Putot